Why people engage in a weight loss intervention at their workplace - a stratified case study - Jeanette Reffstrup Christensen; Majda Pajevic; Pia Maria Ilvig; Karen Søgaard; Christina Jessen-Winge (BMC, 2019)
Abstract Background The prevalence of obesity has increased significantly worldwide within the last decade. As obesity is recognised as a contributing factor when developing various health threatening chronic diseases, prevention initiatives focusing on weight loss are becoming more important. Because of the time spent at the workplace, workplaces can be optimal arenas for weight loss programs and these programs have been effective to decrease body weight. Thus, reasons for engaging in weight loss interventions needs exploring, in order to engage more workplaces in weight loss interventions. Such information provides important knowledge that may help to inform decisions of municipalities, employers and other public health decision makers, when and if implementing weight loss interventions. The aim of this study was therefore to explore reasons for employee engagement in weight loss projects at the workplace and the incentives a municipality, a manager at a home-care centre, and a project manager have to launch such project. Methods A stratified case study was conducted. A representative from the municipality, the manager at a home-care centre, the project manager of the weight loss intervention and six health-care workers were interviewed at the end of a one-year weight loss intervention at the workplace. Data were analysed using Systematic Text Condensation. Results Analysis identified different views and considerations for engaging in a weight loss intervention at the workplace. For the representative of the municipality the possible economical gain of the project was in focus. The project manager and the manager of the home-care centre both reflected mainly on improvement of the healthcare workers health. For the project manager, achieving good scientific results was highlighted as well. However, the employees were influenced by several factors, such as their own health and weight loss, the pressure from the environment and their struggle for recognition. Conclusions This study concluded that if targeting the increasing worldwide obesity problem through workplace initiated weight loss programs, the sales pitch to managements and employers have to be tailored in order to increase the participation and the motivation for the initiative. Trial registration ClinicalTrial.gov: NCT01015716, registration data 14.12.2010 (Prospectively registered).